Towards Resilient Marine Ecosystems: EcoSensitivity as an Operational Model for Strategic Oil Spill Management - Anneliis Kõivupuu; Mihhail Fetissov; Robert Aps; Helen Orav-Kotta; Valtteri Laine; Mirka Laurila-Pant; Merli Rätsep; Jonne Kotta (Journal of Marine Science and Engineering)
Oil spills pose significant threats to marine ecosystems, and while existing tools simulate spill dispersion and predict impacts, they often lack full integration of accident specifics, detailed drift simulations, and thorough impact analyses. This paper presents the EcoSensitivity decision support system, a comprehensive platform designed to improve oil spill responses by integrating immediate and cumulative environmental impact assessments. The EcoSensitivity system addresses these gaps by combining the Accidental Damage and Spill Assessment Model (ADSAM), oil drift modeling, and the PlanWise4Blue (PW4B) application, which enables high-resolution cumulative impact assessments. This unified tool provides decision-makers with rapid, data-driven insights, facilitating a more informed and effective response to oil spills. EcoSensitivity represents a substantial advancement in operational modeling, supporting ecosystem resilience and aiding in strategic planning for marine conservation.